Toxic sunset on the trail of hazardous waste from Subic and Clark - Pimentel, Benjamin 1964-; Lasola, Louella (Philippine Center for Investigative Journalism, 1993)
Shows the hazardous wastes left by U.S. military forces in Subic and Clark bases.